School Resources and the Academic Achievement of Canadian Students - Wei, Yichun; Clifton, Rodney A.; Roberts, Lance W. (Alberta Journal of Educational Research, 2012)
This study estimates the impact of schools’ physical resources and teachers’ academic press on students’ academic achievement in mathematics and reading when a number of important student variables are controlled. Academic press is defined as teachers' emphasis on academic excellence and upholding academic standards (McDill, Natriello, & Pallas, 1986). It is often argued that both school and teacher resources affect the educational achievement of students. But, the research literature has been inconsistent, which may be due to methodological issues. For this reason, this study attempts to correct two of the most important issues by using Canadian national data and multi-level modeling. The results reveal that, in Canada, at least, the physical resources and academic press evaluated by school principals do not significantly affect students’ achievement in mathematics and reading. Cette étude évalue l’impact des ressources physiques des écoles et la rigueur académique des enseignants sur le rendement académique des élèves en mathématiques et en lecture lorsqu’on contrôle un certain nombre de variables importants chez les élèves. On définit la rigueur académique comme l’importance que les enseignants accordent à l’excellence académique et le maintien de normes académiques (McDill, Natriello, & Pallas, 1986). On soutient souvent que tant les ressources de l’école que celles des enseignants jouent un rôle dans le rendement académique des élèves. Les publications de recherche, par contre, sont contradictoires, peut-être en raison de problèmes méthodologiques. Cette étude tente donc de rectifier deux des problèmes les plus importants en employant des données nationales canadiennes et le modelage multiniveau. Les résultats indiquent qu’au Canada du moins, les ressources physiques et la rigueur académique telles qu’évaluées par les directeurs d’école n’affectent pas de façon significative le rendement des élèves en mathématiques et en lecture.